دراسة جودة بحيرة سد الباسل وفقاً لحمولة المغذيات. - كباس ريتا (Latakia University Journal -Engineering Sciences Series, 2018)
يهدف هذا البحث إلى دراسة أهم مؤشرات تلوث المياه المسببة للإثراء الغذائي في بحيرة سد الباسل، وربطها بمصادر التلوث المتركزة على ضفاف البحيرة، والمتمثلة بمياه الصرف الصحي غير المعالجة من القرى المجاورة، ومياه الصرف الزراعي المحملة بالأسمدة المختلفة التي تصل إلى البحيرة مع مياه الأمطار الوافدة من الأراضي الزراعية المحيطة بالمنطقة. وهذه المؤشرات هي تراكيز الفوسفور الكلي، وتراكيز النتروجين الكلي. تمّ أخذ العينات وتحليلها من أربعة مواقع (S1-S2-S3- S4)، خلال دورة هيدرولوجيّة كاملة ابتداءً من كانون الثاني (2016) حتّى كانون الأول .(2016) ونتيجة الدراسة تبين أنّ البحيرة شديدة الإخصاب بحسب المؤشرين (TN- TP)، وهذا يدل على أنّ البحيرة تتأثّر بالملوثات التي تصادفها وخاصة ملوثات مياه الصرف الصحي، وتمّ تعيين العنصر المحدد لنمو الطحالب من خلال معرفة النسبة ما بين النتروجين الكلي والفوسفور الكلي حيث تبين أنّ النسبة TN/TP أكبر من 10 وبالتالي فإن الفوسفور الكلي هو العنصر المحدد لنمو الطحالب في بحيرة سد الباسل. This research aims at studying the most important indicators of water pollution leading to nutrient increase (eutrophication) in AL- Basel Dam Lake, and connecting them with pollution sources represented by untreated sewage water and agricultural drainage water, including rain water coming from the lands surrounding the lake. Among the most important of these indicators are total phosphorus (TP) and total Nitrogen (TN). Samples were taken and analyzed from four sitesof the lake (S1, S2, S3, S4) were conducted periodically. The work continued to conduct tests for full hydrological cycle as of January (2016) until December (2016). The study showed that the lake was highly fertilized according to the (TN- TP) this indicates that the lake is affected by the pollutants it encounters, especially the wastewater pollutants. The specific component of algal growth was determined by knowing the ratio between total nitrogen and total phosphorus. The TN / TP ratio was greater than 10, so total phosphorus is the specific component of algal growth in the Basel DamLake.